A Novel Process for Manufacturing Vanadium Dioxide(VO2) as a resource of Vanadium Electrolyte from Vanadium Pentoxide(V2O5). Issue 3 (4th July 2022) - Kim, Byung-Su; Ryu, Tae-Gong; Choi, Jihyuk; Park, Tae Jun; Chang, Hankwon; Yoo, JeongHyun; Suh, Chang-Youl; Cho, Sung-Wook; Roh, Kimin
ABSTRACT: A vanadium electrolyte for energy storage is generally prepared by dissolving vanadium pentoxide (V2 O5 ) in sulfuric acid using oxalic acid ((COOH)2 ) as a reducing agent. However, there is a disadvantage that the dissolution rate in the sulfuric acid solution of V2 O5 is very slow. In this study, a new process for producing vanadium dioxide (VO2 ), which has the faster dissolution rate than V2 O5 in sulfuric acid solution, was developed. Vanadium dioxide (VO2 ) could be used in the production of a vanadium electrolyte for energy storage. The process developed in the study has the advantages of being economical and simple as compared to the existing process for producing VO2 from V2 O5 using hydrogen or carbon monoxide as a reducing agent.